The Polarization of Orientation Amongst The Local on Cultural Land Utilization for Ecotourism Development in Ranah Minang Sumatera Barat - Adam Rachmatullah; Ricky Avenzora; Tutut Sunarminto (Journal of Regional and City Planning, 2023)
The dynamics of problems related to land occupation, ownership of cultural land, and agricultural land in Indonesia, especially in Ranah Minang, West Sumatra, have become so serious they need to be solved first before trying to achieve the ideals of sustainable development. The research methodology used in this study was a phenomenological approach. The data were analyzed through the One Score-One Criterion Scoring System. The mean values obtained for the phenomenon of cultural land-use patterns in the region were very good in many aspects. On the other hand, the dynamics of stakeholder perceptions, motivations, and preferences did not indicate any directional bias or attitudinal scale among actors over the use of cultural land. This would be different if observed in the dynamics of perception and ecotourism motivation by generating inferences of the direction polarization and attitude scale among actors. The strategy for this purpose was to optimize various aspects of land-use patterns for ecotourism development: 1) strengthening the function of cultural lands as precious treasure; 2) creating a communal business field; 3) optimizing the productivity of agricultural commodities as added value for land users; 4) establishing no-building zones in certain strategic areas as well as providing incentives to land users.